Analisis Faktor Sistem Akuntansi Daerah, Pengendalian Intern dan Sistem Pelaporan Terhadap Akuntabilitas Kinerja Instansi Pemerintah di Kota Tual (Studi Kasus SKPD Kota Tual) - Refalina Alkatiri Puput; Anik Malikah; Junaidi Junaidi (e_Jurnal Ilmiah Riset Akuntansi, 2023)
Government Agency Performance Accountability refers to the responsibility of a government entity to take ownership of both successful and unsuccessful implementation in its efforts to attain predefined objectives and goals. This accountability is manifested through regular government agency performance reports. In order to better understand how government entities are held accountable, the effects of regional accounting systems, internal control systems, and reporting systems will be examined in this study. The study questioned 82 individuals from a set of 15 Tual City-based SKPDs using a purposive sample methodology. Multiple linear regression analysis and a questionnaire were used to collect the data. The results of the F-test demonstrate that governmental entities' accountability is significantly influenced by the regional accounting system, internal controls, and reporting system. To assess the precise effects of each independent variable on the dependent variable, partial tests (t-tests) were performed. The findings of the study point to a considerable impact of the regional accounting system, internal controls, and reporting system on the performance accountability of governmental agencies.Keywords: Regional accounting system, internal control and reporting system, performance accountability of government agencies